Performance of Transformer Insulation Paper in the Presence of Multi Walled Carbon Nanotube (MWCNT) in Palm Oil Methyl Ester (POME) - Nurul 'Izzati, Hashim; Sharifah Masniah, Wan Masra; Shirley, Rufus; Nazreen, Junaidi; Yanuar Zulardiansyah, Arief; Nur Eryshazana, Amirulzaki Hassan (2026)
The reliability of power transformers depends greatly on their insulation systems, which traditionally use Mineral Oil (MO) and Kraft paper. Due to environmental concerns with MO, Palm Oil Methyl Ester (POME) has emerged as a sustainable alternative, though it requires performance enhancement for high-voltage use. This study investigates the effect of adding 0.02 g/L Multi-Walled Carbon Nanotubes (MWCNTs) to POME on the mechanical and dielectric properties of Kraft paper, under both unaged and thermally aged conditions. Tensile strength (TS) was evaluated in both machine (MD) and cross directions (CD), while dielectric strength was assessed using AC Breakdown Voltage (ACBDV) tests per IEC standards. Tensile testing confirmed the anisotropic behavior of Kraft paper, with MWCNT addition improving strength by 13 % in the cross direction and showing only a 1.4 % decrease after aging. In the machine direction, strength remained high with minimal changes. All samples met IEC 60641-3-2 standards. AC breakdown voltage improved by 5.8 % in unaged and 3.0 % in aged MWCNT-treated samples, while aging effects were less severe compared to pure POME samples.